Optical, magnetic and structural analysis of new 2AO-CoO-B2O3 (A = Ba, Sr) glasses. (2022) - N'faoui, F.-E.; Taibi, M.; Aride, J.; Boukhari, A.; Saadaoui, H.; Rouzières, M.
Abstract: The glasses with formula 2AO-CoO-B2 O3 (A = Ba, Sr) were prepared successfully by the conventional melting method. The amorphous state of these glasses was confirmed by X-ray diffraction. The thermal investigation conducted by differential scanning calorimetry (DSC) confirms their vitreous nature. Infrared spectroscopy approves the existence of both BO3 and BO4 groups. The transmittance shows the different optical transitions of the Co 2+ in 2AO-CoO-B2 O3 (A = Ba, Sr) glasses. The calculated gap energy shows that these glasses have wide-band-gaps and can be classified as semiconductor materials. The magnetic measurements were studied as a function of the field and temperature. The predominant interactions in these glasses are antiferromagnetic.